A novel amorphous preparation improved curcumin bioavailability in healthy volunteers: A single-dose, double-blind, two-way crossover study. (June 2021) - Sunagawa, Yoichi; Miyazaki, Yusuke; Funamoto, Masafumi; Shimizu, Kana; Shimizu, Satoshi; Nurmila, Sari; Katanasaka, Yasufumi; Ito, Masashi; Ogawa, Tatsuya; Ozawa-Umeta, Hitomi; Hasegawa, Koji; Morimoto, Tatsuya
Graphical abstract: Highlights: curcuRouge TM is a micro amorphous curcumin formulation with light red color. The bioavailability of curcuRouge TM was 3.7-fold higher than that of Theracurmin® in rats. The bioavailability of curcuRouge TM was 3.4-fold higher than that of Theracurmin® in twelve healthy volunteers. curcuRouge TM achieved C max in a shorter time than Theracurmin® in rats and humans. Abstract: Curcumin derived from Curcuma longa has beneficial pharmacological effects. However, its bioavailability is very low. To improve its bioavailability, we developed a novel amorphous formulation of curcumin, called curcuRouge TM . We investigated the bioavailability of curcuRouge TM and compared its efficiency with that of Theracurmin®. Male Sprague–Dawley rats were orally administered curcuRouge TM or Theracurmin® (10 mg/kg of curcumin). Based on the area under the plasma concentration-time curve, the bioavailability of curcuRouge TM was 3.7-fold higher than that of Theracurmin® in rats. We performed a single-dose, double-blind, two-way crossover study to compare the bioavailability of curcuRouge TM and Theracurmin® (90 mg of curcumin) in 12 volunteers (8 males, 4 females). The bioavailability of curcuRouge TM was 3.4-fold higher than that of Theracurmin®. curcuRouge TM achieved C max in a shorter time than Theracurmin® in both experiments. These findings indicate that curcuRouge TM, an amorphous formulation of curcumin, shows superior bioavailability to that of Theracurmin®.